Learning strategies in nursing sciences: Analysis of gender disparities in a Moroccan educational context - K. Ait Moussa; S. Selmaoui; N. Ouzennou (Educación Médica)
Introduction: The 2013 reform of the nursing education system in Morocco, which introduced the License-Master-Doctorate framework and the establishment of Higher Institutes of Nursing Professions and Health Techniques (ISPITS), aimed to modernize higher education and enhance nursing practices. This study examines gender differences in learning strategies among nursing students, considering Morocco's cultural specificities. Subjects and methods: An exploratory study was conducted with 625 first-year students enrolled in three ISPITS in the Marrakech-Safi region during the first semester of the 2022–2023 academic year. Data were collected using the “Mes Outils de Travail Intellectuel” questionnaire, adapted to the Moroccan context. Statistical analyses employed non-parametric tests, including the Mann–Whitney U test for gender comparisons, and a generalized linear model to control for confounding variables such as the institution of origin and field of study. Results: The findings indicate an overall homogeneity between genders in the use of cognitive, metacognitive, and affective tools, with a statistically significant but weak difference in the “Structuring-Reorganization” dimension (p = 0.044, small effect size). Conclusion: The study highlights a general equity in learning strategies, challenging gender stereotypes. However, the overrepresentation of women (78.2%) in the sample limits the analysis of male behaviors. These findings emphasize the need for inclusive pedagogies tailored to local specificities and mixed-method approaches to further explore sociocultural and educational dynamics. Resumen: Introducción: La reforma de 2013 del sistema de formación en ciencias de enfermería en Marruecos, que introdujo el marco de Licenciatura-Máster-Doctorado y la creación de los Institutos Superiores de Profesiones de Enfermería y Técnicas de Salud (ISPITS), tuvo como objetivo modernizar la educación superior y mejorar las prácticas de enfermería. Este estudio analiza las diferencias de género en las estrategias de aprendizaje de los estudiantes de enfermería, considerando las especificidades culturales de Marruecos. Sujetos y métodos: Se llevó a cabo un estudio exploratorio con 625 estudiantes de primer año inscritos en tres ISPITS de la región de Marrakech-Safi durante el primer semestre del año académico 2022–2023. Los datos se recopilaron utilizando el cuestionario «Mes Outils de Travail Intellectuel», adaptado al contexto marroquí. Los análisis estadísticos emplearon pruebas no paramétricas, incluido el test U de Mann–Whitney para comparar los géneros, y un modelo lineal generalizado para controlar las variables de confusión, como el instituto de origen y la especialidad. Resultados: Los resultados revelan una homogeneidad general entre los géneros en el uso de herramientas cognitivas, metacognitivas y afectivas, con una diferencia estadísticamente significativa pero débil en la dimensión «Estructuración-Reorganización» (p = 0,044, tamaño del efecto pequeño). Conclusión: El estudio destaca una equidad general en las estrategias de aprendizaje, cuestionando los estereotipos de género. Sin embargo, la sobrerrepresentación de mujeres (78,2%) en la muestra limita el análisis de los comportamientos masculinos. Estos resultados subrayan la necesidad de pedagogías inclusivas adaptadas a las especificidades locales y de enfoques mixtos para profundizar en la exploración de las dinámicas socioculturales y educativas.